DIGITAL CONTACT TOOLS IN PROFESSIONAL LIFE: WHAT GOVERNS THE CHOICE? - Selg, Håkan (AoIR Selected Papers of Internet Research, 2015)
A changing communicative environment represents both opportunities and risks to professional organisations. Both public and private bodies are experimenting with the new contact tools in order to adapt them to daily tasks. In a survey of the use of contact tools such as voice calls (landline, mobile, VoIP ), and texts (e-mail, SMS, IM) the respondents were asked to indicate on a Likert-scale their preferences for the respective contact tools depending on context and situations. Taken together, the findings indicate that the choice of contact tools is less contingent on contextual matters as was hypothesised. Instead the results suggest that people choose the tool that they believe is most suitable for the person to be contacted.